Annotation, exploitation and evaluation of parallel corpora TC3 I - Hansen-Schirra, Silvia; Čulo, Oliver; Neumann, Stella (Translation and Multilingual Natural Language Processing, 2017)
Exchange between the translation studies and the computational linguistics communities has traditionally not been very intense. Among other things, this is reflected by the different views on parallel corpora. While computational linguistics does not always strictly pay attention to the translation direction (e.g. when translation rules are extracted from (sub)corpora which actually only consist of translations), translation studies are amongst other things concerned with exactly comparing source and target texts (e.g. to draw conclusions on interference and standardization effects). However, there has recently been more exchange between the two fields - especially when it comes to the annotation of parallel corpora. This special issue brings together the different research perspectives. Its contributions show - from both perspectives - how the communities have come to interact in recent years.